Left realist criminology: strengths, weaknesses and the feminist critique - Schwartz, Martin D. (Crime, law and social change, 1991)
Although there is an already large British literature both supporting and attacking left realism, and a growing North American interest on the subject among criminologists, there has been surprisingly little written which attempts to locate both the strengths and weaknesses of the left realist position on crime control. Perhaps the place where the left realists may be weakest is in response to a feminist critique. Actually, it is not only left realism but the socialist left in general which has been unsuccessful in providing adequate responses to the issues brought forth by feminists. This paper attempts to locate the position of left realism within the left criminology debate, and to find its strong and weak points. Further, it attempts to explicate the feminist critique, and to suggest responses critical criminologists might explore, such as those proposed by peacemaking criminology. *** DIRECT SUPPORT *** AW502012 00004